Modern methods of market size estimation - Ziubanova, D. M.; Kovshik, V. I. (НТУ "ХПІ", 2011)
In the article the main approaches to determining market size in marketing research process are examined and peculiarities of their usage are analyzed. Influence of various factors on the process of obtaining marketing information is considered. The importance of taking into account the scale of the enterprise and resources available for research when choosing an approach to the estimation of market size to increase the effectiveness of company's marketing system is distinguished. In the absence of universal approach the scheme of selection of market assessment method based on of those factors is proposed.

У статті розглядаються основні підходи до визначення розміру ринку в процесі маркетингового дослідження i аналізуються особливості їх застосування. Висвітлюється вплив різноманітних факторів на процес отримання маркетингової інформації. Зазначається важливість врахування масштабiв діяльності підприємства та наявних ресурсів для здійснення дослідження при виборi підходу до оцінки і ринку з метою підвищення ефективностi системи маркетингу компанії. В зв'язку з вiдсутнiстю універсального пiдходу пропонується схема вибору методу оцінки ринку виходячи з наведених факторiв
Keywords: market; marketing research; marketing information; enterprise; company's marketing system; assessment methods